2015
DOI: 10.1152/ajpgi.00304.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic TLR4 signaling in obese NAFLD

Abstract: fatty liver disease occurs frequently in the setting of metabolic syndrome, but the factors leading to nonalcoholic steatohepatitis (NASH) are not fully understood. This study investigated Toll-like receptor 4 (TLR4) signaling in human liver with the goal of delineating whether activation of this pathway segregates those with nonalcoholic fatty liver from those with NASH. Experiments were performed using liver biopsy tissue obtained from class III obese subjects undergoing bariatric surgery, and extended to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(170 citation statements)
references
References 41 publications
6
150
1
2
Order By: Relevance
“…Consistent with other recent reports, we identified enhanced hepatic gene expression of key IFN-I regulatory factors, IRF3 and IRF7, during DIO and/or NAFLD, (36, 37). While previous studies used knock-out mice to examine the role of individual IRFs associated with IFN-I pathways and their effects on glucose metabolism (36, 38, 39), we utilized HFD-fed IFNαR1 knock-out mice to broadly eliminate IFN-I and showed that IFN-I responses, as a whole, promote obesity-related IR.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other recent reports, we identified enhanced hepatic gene expression of key IFN-I regulatory factors, IRF3 and IRF7, during DIO and/or NAFLD, (36, 37). While previous studies used knock-out mice to examine the role of individual IRFs associated with IFN-I pathways and their effects on glucose metabolism (36, 38, 39), we utilized HFD-fed IFNαR1 knock-out mice to broadly eliminate IFN-I and showed that IFN-I responses, as a whole, promote obesity-related IR.…”
Section: Discussionsupporting
confidence: 92%
“…59 In addition, TLR4 and IRF3 expression (MyD88 pathway) appear to be upregulated in the liver of patients suffering from NASH versus NAFLD, which is associated with increased lipopolysaccharides (LPS) and fatty acid levels. 60 In accordance with the bile acid profile, we found that specific bacterial genera were different between LKO and WT mice during normal chow diet. Sutterella and Allobaculum were decreased in LKO-CT mice and HFD-fed mice.…”
Section: Discussionsupporting
confidence: 69%
“…It has been demonstrated that bacterial LPS enhances hepatic fatty acid synthesis, while inhibiting fatty acid oxidation in liver by reducing FABP gene expression [67]. Thereby, TLR-4 expression upregulation correlated with increased LPS and fatty acids, and associated with induced de novo lipogenesis in NAFLD patients [68]. Thus, TLR-4 plays a critical role in glucose and lipid metabolism and, in turn, free fatty acids have been reported as agonists for TLR-4 [69,70], inducing activation of inflammatory transcription factors as NF-B [69].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%